Structural analysis of software industry organizations in Turkey - Başol, Esra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Information Technology is one of the fastest growing industries in recent years, creating significant opportunities to the economies of countries. The software industry, a sub-field of information technology, performs extreme progress in all over the world. Even though Indian, Israeli, and Irish software industry have captured the essential portion of the world trade, well-developed countries provides a large revenues through software industry. Even though the software industry in Turkey has started to develop later than other countries, it is expected that the software industry will enhance accelerated growth in the future years. The success and development of software industry is critical for the growth of economy. The purpose of this study is to determine the organizational structural determinants affecting the organizational effectiveness of the software industry in Turkey. In this study, a research model is developed based on the examination of the literature. The research survey has been prepared regarding the conceptual model and software companies were surveyed. The validity and reliability of the questionnaire, Cronbach's alpha coefficient was tested. Regression analysis was conducted to determine the affect of organizational structural determinants on organizational effectiveness. In addition to regression analysis, the organizational structure and effectiveness are assessed regarding organizational age, and size, obligation to regular audit and the level of hierarchy.
Keywords: Computer software industry -- Turkey.; Computer industry -- Turkey.